Kilka głosów o czasopiśmiennictwie rosyjskim początku XIX wieku - Dąbrowska, Magdalena (Przegląd Rusycystyczny, 2013)
Magdalena Dąbrowska Uniwersytet Warszawski, Warszawa, Poland dabrowska_m@o2.pl НЕСКОЛЬКО ВЫСКАЗЫВАНИЙ О РУССКОЙ ПЕРИОДИЧЕСКОЙ ПЕЧАТИ В НАЧАЛЕ XIX ВЕКА Резюме Статья посвящена процессам становления теоретических знаний о периодических изданиях в России в начале XIX века. Она состоит из трех частей: 1) вступление (периодизация; анализ Рассуждения об обязанностях журналистов… Михаила Ло-моносова, 1755; и др.); 2) рассмотрение статей, напечатанных в журналах „Лицей” (Полезны ли журналы? Ивана Мартынова, 1806), „Санкт-Петербургский вестник” (Нечто о журналах Дмитрия Дашкова, 1812) и „Вестник Европы” (Нечто о журналах, 1815); 3) заключение (принцип эпохи Просвещения „приятное и полезное”, развитие литературной критики; и др.). THE SEVERAL VOICES ABOUT THE RUSSIAN PERIODICAL PRESS IN THE EARLY 19TH CENTURY Summary The article presents the formation process of the theoretical views on the periodical press in Russia in the early 19th century. It consists of three parts: 1) the introduction (periodiza-tion, analysis of the Dissertation on the Duties of Journalists… by Mikhail Lomonosov, 1755, etc.); 2) the analysis of the articles in the periodicals “Licey” (Are the magazines useful? by Ivan Martinov, 1806), “Sankt-Peterburskij vestnik” (Few words on magazines by Dmitry Dashkov, 1812) and “Vestnik Evropy” (Few words on magazines, 1815); 3) the conclusions (principle of the Enlightenment period “Pleasant and Useful”, development of the literary criticism etc.).